Numerical solutions of 2-D steady incompressible driven cavity flow at high Reynolds numbers - Erturk, E; Corke, TC; Gökçöl, C (John Wiley & Sons Ltd, 2005)
Numerical calculations of the 2-D steady incompressible driven cavity flow are presented. The Navier-Stokes equations in streamfunction and vorticity formulation are solved numerically using a fine uniform grid mesh of 601 x 601. The steady driven cavity flow solutions are computed for Re <= 21000 with a maximum absolute residuals of the governing equations that were less than 10(-10). A new quaternary vortex at the bottom left corner and a new tertiary vortex at the top left corner of the cavity are observed in the flow field as the Reynolds number increases. Detailed results are presented and comparisons are made with benchmark solutions found in the literature. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: steady 2-D incompressible N-S equations; driven cavity flow; fine grid solutions; high Reynolds numbers